Impact of ChAdOx1 nCoV-19 (Covishield™) Vaccination: How Long Will It Persist? - Devi, Leimapokpam Sumitra; Sardar, Moumita; Sharma, Mukesh; Khandait, Manisha (International Journal of Microbiology, 2022)
An increase in COVID-19 immunization coverage has been linked to a decrease in the average case fatality rate. As a result, further research is needed to determine the persistence and duration of vaccine-induced protective antibodies in order to assess the effectiveness of COVID-19 vaccinations. The present study aimed to determine the COVID-19 IgG antibodies among healthcare workers (HCWs) before and after the ChAdOx1 nCoV-19 (Covishield™) vaccination. A total of 150 HCWs who had received the Covishield™ vaccine were assessed after obtaining written informed consent. Blood samples were drawn at three time points, namely, within one week prior to first dose of vaccination, prior to second dose of vaccination (28–33 days after the first dose of vaccination), and 90–95 days after the second dose of vaccination for detecting neutralizing antibodies, i.e., IgG antibodies by ELISA. The overall baseline seropositivity among the HCWs was found to be 28% (n = 42), assessed by the sample collected prior to first dose of COVID-19 vaccination. The seroconversion rate was reported to be 80% (n = 120) one month after the first dosage and increased to 92.7% (n = 139) three months later. Additionally, there was a significant gradual increase in the IgG concentrations postvaccination in majority of the study participants. In those HCWs who had prior history of SARS-CoV-2 infection, significantly higher antibody level was observed compared to antibody-naive individuals. Fever, pain or swelling at the site of injection, and headache were the most frequently reported adverse events following vaccination among the study participants. Regardless of prior SARS-CoV-2 positivity, two doses of the CovishieldTM vaccine elicited a protective neutralizing antibody response that lasted for three months after the second dose of vaccination.